PENGARUH SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN SISTEM PENGUKURAN KINERJA TERHADAP KINERJA MANAJERIAL PADA PUSKESMAS SITANGGAL - Eduward Tony Sitorus; Risma Ayu Nabela; Oktavia Marpaung; Ringkot P Nainggolan (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This research aims to analyze the influence of accounting information systems and performance measurement systems. The method used in research using quantitative research is research that is described systematically, directed and clearly structured from the beginning to the formation of the research design. The sample is nonprobability sampling using a saturated sample. The population in this study was the Siangkat Community Health Center. The sample in the study was 30 samples. Data used in This research uses primary data sourced from the Sitanggal Community Health Center. Results of this research: partially (t test) it is known that the Accounting Information System and Performance Measurement System have a significant effect on Managerial Performance, and in the F test the Accounting Information System and Performance  Measurement System variables simultaneously have an effect on Managerial performance. In the coefficient of determination, there is an influence of motivation and work discipline on employee performance which is influenced by other factors which are not included in the variables in this research.